Money, Financial Institutions and Macroeconomics - Cohen, Avi; Hagemann, Harald; Smithin, John (Recent Economic Thought, 1997)
Money, Financial Institutions and Macroeconomics presents a comparative and international perspective on the current state of research in monetary theory, and the application of monetary theory to important policy issues. The main emphasis is on views stressing the importance of credit creation in the monetary process, in a tradition which arguably encompasses Wicksell, the later Swedes and the Austrians, through the later Hicks, the circuit school and contemporary post-Keynesians. In addition, however, there are distinguished contributions from economists with a more 'mainstream' approach to the issues. The book is subdivided into four main parts: Part I reviews the theory of a monetary and credit economy; Part II explores alternative views on money and credit; Part III deals with monetary policy issues in North America; and Part IV discusses monetary policy issues in Europe. 'Taken together, the contributions to this volume certainly bear out Hick's famous adage about the much closer relationship between 'monetary theory' and 'monetary history' than is the case in other branches of economic thought.'